Strategies for building trust in news: What the public say they want across four countries - Banerjee, S; Mont’Alverne, C; Ross Arguedas, A; Toff, B; Fletcher, R; Nielsen, RK (Reuters Institute for the Study of Journalism, 2023)
This report investigates what the public wants and expects from news media when it comes to trustworthy journalism, drawing on original surveys collected in the summer of 2023 in Brazil, India, the United Kingdom, and the United States. The report examines how different segments of the public are receptive to a variety of approaches to repairing trust in news. These approaches range from editorial practices and transparency initiatives to reforming the way newsrooms are led and managed as well as the way news outlets engage with the public. Findings suggest that broadly audiences favour each type of approach, but that particular efforts are especially prioritised by different subgroups. This is especially the case with respect to newsroom diversity and concerns over one-sidedness in coverage. Different segments of the public raise distinct concerns in these areas and want see news organisations take different steps toward solving these issues.